Kelestarian haiwan liar - Norsuhana Abdul Hamid; Dewan Bahasa dan Pustaka (Kuala Lumpur : Dewan Bahasa dan Pustaka, 2018)
On wild animals and environmental conditions in Malaysia.
Includes bibliographical references (pages 177-182) and index.
In Malay.
Keywords: Animals; Urban animals